2022
DOI: 10.1126/scitranslmed.abj4375
|View full text |Cite
|
Sign up to set email alerts
|

Senolytic treatment preserves biliary regenerative capacity lost through cellular senescence during cold storage

Abstract: Liver transplantation is the only curative option for patients with end-stage liver disease. Despite improvements in surgical techniques, nonanastomotic strictures (characterized by the progressive loss of biliary tract architecture) continue to occur after liver transplantation, negatively affecting liver function and frequently leading to graft loss and retransplantation. To study the biological effects of organ preservation before liver transplantation, we generated murine models that recapitulate liver pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 88 publications
0
10
0
Order By: Relevance
“…To treat aged liver specimens, approaches, such as the use of senolytics with or without machine perfusion to restore old or damaged liver tissue, have been reported. 33 Several agents, such as quercetin, can reportedly eliminate senile cells that exert a detrimental effect on the liver. 34 Other reports have demonstrated the utility of stem cell therapy to strengthen and recondition aged liver tissue before implantation or even before donor surgery in countries where deceased donors are scarce.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To treat aged liver specimens, approaches, such as the use of senolytics with or without machine perfusion to restore old or damaged liver tissue, have been reported. 33 Several agents, such as quercetin, can reportedly eliminate senile cells that exert a detrimental effect on the liver. 34 Other reports have demonstrated the utility of stem cell therapy to strengthen and recondition aged liver tissue before implantation or even before donor surgery in countries where deceased donors are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…To treat aged liver specimens, approaches, such as the use of senolytics with or without machine perfusion to restore old or damaged liver tissue, have been reported 33 . Several agents, such as quercetin, can reportedly eliminate senile cells that exert a detrimental effect on the liver 34 .…”
Section: Discussionmentioning
confidence: 99%
“…PTEN deficiency causes PICS without initiating DDR via the PI3K/AKt/mTOR-p53-p21 signaling pathway. Mammalian rapamycin target complexes 1 and 2 (mTORC1 and mTORC2) interact with the mouse double minute 2 (MDM2) homolog to control p53 by direct phosphorylation and, subsequently, accumulation of p21 induces senescence [ 70 ]. PICS is convenient for pro-senescent cancer therapy, as it is not followed by typical hyperproliferation or DDR.…”
Section: The Various Types Of Senescencementioning
confidence: 99%
“…7 The work by Stuart J. Forbes and coworkers in Science Translational Medicine contributes to another milestone in the "senescence story" demonstrating that the depletion of senescent cells preserved biliary architecture and regenerative capacities in cold storage preserved livers. 8 The authors observed that hepatocytes and cholangiocytes (epithelial cells representing the inner lining of bile ducts) behaved differently in response to cold storage. Although prolonged cold storage did not alter the gross anatomy of the liver, detachment of cholangiocytes into the lumen was observed.…”
Section: Targeting Cellular Senescence In Organ Transplantationmentioning
confidence: 99%